Phytoplankton Inventory and Diversity in Floating-Net-Cages Area of Lake Maninjau, West Sumatra (International Journal of Scientific Research and Management (IJSRM), 2020)
A study on inventory and diversity of phytoplankton in the floating-net-cages area of Lake Maninjau has been carried out from five different sites (Muko-muko, Koto Kaciak, Kubu Baru, Tanjung Sani, Sigiran). Sampling was conducted in the surface water and incubation zone (Secchi depth) from each site, start from November 2017 to January 2018. This study aims to identify phytoplankton species and diversity, also habitat quality due to floating-net-cages activities in Lake Maninjau. A standard method was followed in this study to identify phytoplankton species and calculated the biological index. Other factors recorded including the characteristic of aquatic habitat, temperature, TDS, TSS, and pH. From the observation, we found 17 species of phytoplankton consist of 4 Classes. Phytoplankton diversity index (H’) ranged from 2.42 to 2.62 with the highest diversity index found in Muko-Muko and Sigiran (2.42 and 2.62) while the lowest in Koto Kaciak and Tanjung Sani (1.63 and 2.18). Phytoplankton Evenness index (E) ranged from 0.41 to 0.67 with the highest value found in surface water and incubation zone in Muko-Muko and Sigiran (0.64 and 0.67, respectively) while the lowest found in Koto Kaciak (0.41 and 0.60, respectively). Phytoplankton dominance index (D) ranged from 0.87 to 0.92 with the highest dominance index found in surface water and incubation zone in Sigiran, Muko-Muko, Koto Kaciak, and Kubu Baru (0.90) and Sigiran (0.92) while the lowest found in Tanjung Sani (0.89 and 0.87). From this study, we can conclude that feed residue from floating-net-cage activity causes impairment in water quality and can be detected from the physical-chemical factors of Lake Maninjau.